Frankie performed the following steps to solve the equation 2m2−24m=−54

  1. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m^2−24m+54=0 Step 2: 2(m^2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 95 views
  2. Frankie performed the following steps to solve the equation 2m^2−24m=−54Step 1: 2m^2−24m+54=0 Step 2: 2(m^2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 52 views
  3. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m2−24m+54=0 Step 2: 2(m2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 192 views
  4. 6)Frankie performed the following steps to solve the equation 2m2−24m=−54 . Step 1: 2m2−24m+54=0 Step 2: 2(m2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 43 views
  5. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m2−24m+54=0 Step 2: 2(m2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 106 views
  6. Frankie performed the following steps to solve the equation 2m²-24m = -54.Step 1: 2m² 24m+54 -0 Step 2: 2 (m² - 12m +27) = 0
    1. answers icon 1 answer
    2. views icon 64 views
  7. Frankie performed the following steps to solve the equation 2m ^ 2 - 24m = - 54 . Step 1: 2m ^ 2 - 24m + 54 = 0 Step 22 (m ^ 2 -
    1. answers icon 1 answer
    2. views icon 36 views
  8. Frankie performed the following steps to solve the equation 2m^2−24m=−54Step 1: 2m^2−24m+54=0 Step 2: 2(m^2−12m+27)=0
    1. answers icon 1 answer
    2. views icon 23 views
  9. Frankie performed the following steps to solve the equation 2m ^ 2 - 24m = - 54 . Step 1: 2m ^ 2 - 24m + 54 = 0 Step 22 (m ^ 2 -
    1. answers icon 1 answer
    2. views icon 40 views
  10. Frankie performed the following steps to solve the equation 2m²-24m = -54.Step 1: 2m² 24m+54 -0 Step 2: 2 (m² - 12m +27) = 0
    1. answers icon 1 answer
    2. views icon 56 views